Quantifying the importance of multi‐scale management and environmental variables on moorland bird abundance. (10th May 2017) - Buchanan, Graeme M.; Pearce‐Higgins, James W.; Douglas, David J.T.; Grant, Murray C.
Abstract : UK moorlands are semi‐natural habitats managed for a mix of livestock, game shooting and forestry, among other activities. An assessment of the importance of characteristics that correlate with moorland bird populations of high conservation importance can inform appropriate management at appropriate locations. We use hierarchical partitioning to assess the absolute and relative importance of climate, topography, soil, landscape management (wider scale habitat configuration of forestry and agriculture) and site‐based management (indices of predator control, and vegetation characteristics) in determining the abundance of a suite of upland birds in four regions of the UK. Unmeasured region‐specific effects often made the largest contribution to models. Physical characteristics (climate, topography, soil) were important and on average explained a similar amount of variation to site‐based management. However, there was considerable interspecific variation in the importance of both. Landscape‐scale variables were generally of low importance. An index of predator control was positively correlated with the abundance of Red Grouse Lagopus lagopus scotica and two waders. Vegetation characteristics (composition and structure) were, together, strong correlates of the abundance of passerine species. Vegetation characteristics were as important as indices of predator control for waders and grouse. The importance of regional effects, physical characteristics and variables relating to management suggest targeting site‐based management (such as predator control or vegetation management) to the areas where physical characteristics are most favourable. The most beneficial management will vary between species, necessitating a mosaic of management options across upland areas to benefit all species.